Nucleolin as a potential biomarker for canine malignant neoplasia. (March 2021) - Cruz, Carla; Pedro, Augusto Q.; Carvalho, Josué; Santos, Tiago; Talhada, Daniela; Paiva, Artur; Queiroz, João A.; Andrade, Mónica; Pinto, Marta; Montenegro, Luís; Delgado, Leonor; Pereira, Patrícia
Abstract: Human nucleolin (NCL) is a multifunctional protein that is involved in diverse pathological processes. Recent evidences have shown that NCL is markedly overexpressed on the surface of most human cancer cells when compared to normal cells, being overexpressed in several malignant cells. Based on the exposed, the purpose of this pilot study is to investigate the expression pattern of NCL in canine malignant neoplasia and control groups. NCL expression at both messenger RNA and protein levels in the subcellular fractions were respectively detected by RT-PCR and western blotting, allowing to infer the NCL positivity rate in canine neoplasia. The identity of NCL amplicons obtained by RT-PCR was confirmed by Sanger sequencing and found to correspond to Canis lupus familiaris . Using flow cytometry, the blood cells expressing NCL from canine neoplasms were also identified using several cell surface markers and their levels quantified. These results showed that NCL expressed in lymphocytes, monocytes and neutrophils in dogs with malignant neoplasia is higher (> 50%) when compared with the control group. We found an increased expression of surface and cytoplasmic NCL in canine malignant neoplasia group, while nuclear NCL is predominantly found in the control group. Overall, this study discloses and identifies for the first time the presence of NCL in canine blood. Highlights: Nucleolin is markedly expressed in PBMCs cells of dogs with neoplasia. Nucleolin mRNA expression in canine PBMCs is higher than controls. Higher mass bands of nucleolin were detected in PBMCs of canine neoplastic. T-cell lymphoma has nucleolin expression higher in all cells analyzed. Nucleolin amplicons obtained by RT-PCR was confirmed by Sanger sequencing.